Flocculation efficiency analysis of varius inorganic and organic flocculants in harvesting nannochloropis sp and tetraselmis tetrahele. - Ledesma, Luvic M. (College of Fisheries, 2010)
In this study harvesting microalgae species of nannochloropsis sp and tetraselmis tetrahele through with the use of different inorganic and organic flocculants was carried on. Eight flocculants were tested at different levels of concentration and inorganic flocculants showed to be most efficient in aggregating microalgal cells. Commercial alum and AI2 (SO4)3 showed to be the most efficient in both microalgal treatments both in flocculating efficiency and setting time. NaOH showed to raise pH levels significantly higher (p<01) in both treatments but causes low flocculation. However, the use of tealeaves or Ehretia microphylla as a flocculant is seen to have great potential in optimum concentration. Microalgal cells in all treatments under physical under microscopic examination showed no structural damage and are physically healthy. The significant (p<0.01) change in pH shown to be on the tolerable range for microalgal reculturing.